Mood response after two weeks of rapid weight reduction in judoka - Fortes, L.; Lira, H.; Andrade, J.; Oliveira, S.; Paes, P.; Vianna, J.; Vieira, L. (Archives of Budo, 2018)
Background and Study Aim: It is common for judo athletes to use methods for rapid weight loss in the days preceding competitions in an attempt to create a supposed advantage by being able to compete in lower body weight categories. The aim of the study was the mood response in judo athletes after two weeks of rapid weight reduction.